Case-Control Pilot Study on Acute Diarrheal Disease in a Geographically Defined Pediatric Population in a Middle Income Country - Ana E. Farfán-García; Chengxian Zhang; Aamer Imdad; Monica Y. Arias-Guerrero; Nayibe T. Sánchez-Alvarez; Rikhil Shah; Junaid Iqbal; Maria E. Tamborski; Oscar G. Gómez-Duarte (Hindawi Limited, 2017)
Introduction. Acute diarrheal disease (ADD) is a common cause of morbidity and mortality in children under 5 years of age. Understanding of the etiology of ADD is lacking in most low and middle income countries because reference laboratories detect limited number of pathogens. The objective of this study was to determine the feasibility to conduct a comprehensive case-control study to survey diarrheal pathogens among children with and without moderate-to-severe ADD. Materials and Methods. Microbiology and molecular-based techniques were used to detect viral, bacterial, and parasitic enteropathogens. The study was conducted in Bucaramanga, Colombia, after Institutional Review Board approval was obtained. Results. Ninety children less than 5 years of age were recruited after a written informed consent was obtained from parents or guardians. Forty-five subjects served as cases with ADD and 45 as controls. Thirty-six subjects out of 90 (40.0%) were positive for at least one enteropathogen, that is, 20 (44.4%) cases and 16 (35.5%) controls. Conclusions. The three most common enteric pathogens were enteroaggregative E. coli (10.0%), Norovirus (6.7%), and Salmonella spp. (5.6%). The E. coli pathogens were 18.8% of all infections making them the most frequent pathogens. Half of ADD cases were negative for any pathogens.